(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Currently, six species of Giardia are recognized, among which the ones responsible for human disease are L. intestinalis (syn. Giardia duodenalis, G. lamblia, Giardia intestinalis). The introduction of molecular-genetic diagnostic methods has identified eight main genetic subtypes of L. intestinalis (A–H). Human giardiasis is associated with subtypes A and B, which also exhibit intragroup variations (AI–AIII, BIII–B1V) [7]. Giardia that infect humans can also infect other mammalian species, both in the wild and in domestic animals.